EFFECT OF MOTIVATION ON EMPLOYEE SATISFACTION IN ALAS WATU EMAS BANGKINANG - Novarina, Novarina; Basem, Zamhir; Setiawan, Adi (Jurnal Riset Manajemen Indonesia, 2023)
This study aims to determine the effect of motivation on employee job satisfaction at PT. Alas Watu Emas Bangkinang, Kampar Regency. The sample of this study used a saturated sampling technique (census), namely 60 employees at PT. Alas Watu Emas Bangkinang, Kampar Regency. The data collection techniques used were questionnaires and research files. The data analysis technique used is simple regression analysis with a significant level (α) of 0.05. The results of this study conclude that motivation has a significant effect on employee job satisfaction, with a significant value less than 0.05. The contribution of the independent variable to the dependent variable is strong